Needs Analysis for the Development of Interactive Infographic Media on Painting Materials in Cultural Arts Subjects for Grade IX Junior High School - Suyono Suyono; Makmum Raharjo; Deris Stiawan (FKIP - Universitas Riau, 2026)
Painting instruction in Cultural Arts subjects is inherently visual and procedural, requiring interactive and contextual media to effectively support students’ creative development. However, learning practices at the junior high school level are still largely dominated by conventional approaches that inadequately visualize technical processes. This study aimed to analyze the need for developing interactive infographic media for Grade IX painting materials at SMP Negeri 1 Jirak Jaya. A descriptive quantitative method was employed using a survey involving 32 students and 2 Cultural Arts teachers. Data were collected through questionnaires addressing learning experiences, difficulties, media preferences, resource accessibility, teacher readiness, and evaluation needs. The results show that 87.5% of students prefer visual-interactive media, and 81.3% favor hands-on practice supported by digital visualization. However, 68.8% experience difficulties mastering techniques independently, and 62.5% report limited access to structured online resources. Teachers demonstrate positive acceptance of interactive infographic media, emphasizing user-friendly design and integrated formative evaluation features. In conclusion, there is a clear gap between procedural learning demands and existing instructional support, indicating the need to develop scaffolded, visually structured, and evaluation-integrated interactive infographic media to enhance Grade IX Cultural Arts learning.